A bi-virus competing model with time-varying susceptibility and repeated infection. (October 2022) - Luo, Guoqiang; Zhai, Shidong; Zhou, Ping; Tao, Junli
Abstract: This paper introduces a bi-virus model with time-varying susceptibility. The model describes the case that there coexist two viruses and the time-varying susceptibility due to repeated infections. For different parameters, we investigate the stability of various equilibriums. Under appropriate conditions the two viruses show competitive relationship, that is, one virus will eventually become a pandemic, and the other virus will eventually disappear. For this case, we further study the dynamical behavior of virus transmission. The model shows some new phenomena, that is, the outbreak of the virus will be delayed appropriately, giving people an illusion. Finally, we present a numerical example to illustrate the effectiveness of the theoretical results.